2002
DOI: 10.1103/physrevlett.88.167004
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and Field Dependence of the Anisotropy ofMgB2

Abstract: The anisotropy gamma of the superconducting state of high quality single crystals of MgB2 was determined, using torque magnetometry with two different methods. The anisotropy of the upper critical field was found to be temperature dependent, decreasing from gamma approximately 6 at 15 K to 2.8 at 35 K. Reversible torque data near T(c) reveal a field dependent anisotropy, increasing nearly linearly from gamma approximately equal to 2 in zero field to 3.7 in 10 kOe. The unusual temperature dependence is a true b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
267
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(312 citation statements)
references
References 37 publications
(41 reference statements)
41
267
4
Order By: Relevance
“…17 but with a slightly different thermal treatment, described in Ref. 18. The high quality of similar crystals from the same batch was confirmed by single crystal Xray diffraction and energy dispersive (EDX) X-ray analysis.…”
Section: Sample and Experimentsmentioning
confidence: 78%
“…17 but with a slightly different thermal treatment, described in Ref. 18. The high quality of similar crystals from the same batch was confirmed by single crystal Xray diffraction and energy dispersive (EDX) X-ray analysis.…”
Section: Sample and Experimentsmentioning
confidence: 78%
“…This value is less than in polycrystalline MgB 2 films and in single crystal MgB 2 (γ = 6-9) 30 and significantly higher than that for any thicker clean epitaxial films (γ = 1.2). 31 It is interesting to note that, as film thickness decreases, the c lattice parameter increases slightly from the bulk value because of the small buckling of ab planes (as estimated from TEM measurements). We believe that this results in a strong π scattering caused by the disturbed p z π orbitals, and hence can explain the scenario of a dirtier π band limit, as suggested by Braccini et al 32 In summary, we have demonstrated that high quality ultrathin MgB 2 superconducting films can be fabricated by the HPCVD method followed by Ar ion-milling.…”
mentioning
confidence: 99%
“…In particular, MgB 2 is the first example of a superconductor showing two distinct superconducting gaps [4]. The two-gap nature is revealed in the macroscopic properties of MgB 2 through a pronounced temperature dependence of the anisotropy of the upper critical field [5,6,7,8]. The effect of the two-gap structure on vortex dynamics is presently under intense investigation.…”
mentioning
confidence: 99%